2016
DOI: 10.1007/s11239-016-1370-3
|View full text |Cite
|
Sign up to set email alerts
|

Catheter-directed ultrasound-accelerated thrombolysis may be life-saving in patients with massive pulmonary embolism after failed systemic thrombolysis

Abstract: The treatment options for high risk acute pulmonary embolism (PE) patients with failed systemic thrombolytic treatment (STT) is limited. The clinical use of catheter directed thrombolysis with the EkoSonic Endovascular System (EKOS) in this population has not been evaluated before. Catheter directed thrombolysis is an effective treatment modality for high risk PE patients with failed STT. Thirteen consecutive patients with failed STT were included in the study. EKOS catheters were placed and tissue plasminogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Conversely, if further pharmacologic thrombolysis is desired following primary PMT, an extended thrombolytic infusion can still be performed. 19,20 Even more, after fragmentation, a greater surface area of thrombus can be exposed to the thrombolytic; consequently, less drug and perhaps less time is needed to achieve thrombolysis. However, although we failed to show any difference hospital survival in patients with or without thrombolytic therapy, there is a trend to increased mortality in patients who received thrombolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, if further pharmacologic thrombolysis is desired following primary PMT, an extended thrombolytic infusion can still be performed. 19,20 Even more, after fragmentation, a greater surface area of thrombus can be exposed to the thrombolytic; consequently, less drug and perhaps less time is needed to achieve thrombolysis. However, although we failed to show any difference hospital survival in patients with or without thrombolytic therapy, there is a trend to increased mortality in patients who received thrombolysis.…”
Section: Discussionmentioning
confidence: 99%
“…32 Catheter-directed thrombolysis has proved lifesaving in patients with failure of systemic thrombolysis. 33 We believe the time is rapidly approaching for the implementation of CDT as a first-line therapy for submassive PE. We demonstrate the efficacy of ultrasound-assisted CDT in significantly lowering pulmonary vascular obstruction ( Figure 2) and right ventricular strain (Figure 3) as well as reversing right ventricular hypokinesis and dilation.…”
Section: Discussionmentioning
confidence: 99%
“…However, this invasive procedure is rather time-consuming and may not be available in all hospitals. Sag et al 23 . showed that CDT is an effective alternative in patients with failed ST, leading to improvement of clinical outcomes and echocardiographic parameters at a low complication rate.…”
Section: Catheter-based Therapies In High-risk Pulmonary Embolism Patmentioning
confidence: 99%